Improvements in assessing the forecasts accuracy - a case study for Romanian macroeconomic forecasts - Mihaela, Bratu (Simionescu) (Serbian Journal of Management, 2013)
This study recommends the use of new measures of accuracy for point forecasts (radical of order n of the mean of squared errors, mean for the difference between each predicted value and the mean of the effective values, ratio of radicals of sum of squared errors (RRSSE- for forecasts comparisons, different versions of U2 Theil’s statistic) and for forecast intervals (number of intervals including the realization, difference between the realization and the lower limit, the upper one, respectively the interval centre). Comparisons are made to present the differences in results determined by the application of the classical measures of predictions accuracy for the inflation and unemployment rate forecasts provided for Romania by Institute for Economic Forecasting (IEF) and National Commission of Prognosis (NCP) on the horizon 2010-2012 and the values of new point forecasts accuracy measures.  The hierarchy of predictions provided by the classical indicators and by the new ones are different. A novelty in literature is also brought by the methods of building the forecasts intervals. In addition to the classical interval based on historical error method, some new techniques of building forecasts are used: intervals based on the standard deviation and those constructed using bootstrap technique bias-corrected-accelerated (BCA) bootstrap method.
Keywords: statistics; square; Means; forecasting; error; classics; assessment; accuracy